2011
DOI: 10.1159/000332734
|View full text |Cite
|
Sign up to set email alerts
|

Focal Functional and Microstructural Changes of Photoreceptors in Eyes with Acute Zonal Occult Outer Retinopathy

Abstract: Purpose: Acute zonal occult outer retinopathy (AZOOR) is characterized by an acute zonal loss of outer retinal function with minimal ophthalmoscopic changes in one or both eyes. We present a patient with AZOOR whose ultrastructural and functional findings were followed for 8 months. Case: A 22-year-old woman developed an acute central scotoma in her right eye. Her best-corrected visual acuity (BCVA) was 0.5 OD and 1.2 OS. The ophthalmoscopic examinations, fluorescein angiography, and full-field electroretinogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
(29 reference statements)
1
16
0
Order By: Relevance
“…The authors suggested that the cone photoreceptor OS dysfunction could be initially reflected by the indistinctiveness of the OS/RPE (COST) line and the absence of foveal bulge and that abnormalities in the IS/OS junction may follow these changes in the more advanced stages. So et al [133] also reported loss of the OS/RPE (COST) line in acute phase AZOOR. In the acute phase, selective loss of the IS/OS and the OS/RPE (COST) lines corresponded with reduced visual acuity and mfERG potentials in areas of visual field defects.…”
Section: Acute Phasementioning
confidence: 93%
See 1 more Smart Citation
“…The authors suggested that the cone photoreceptor OS dysfunction could be initially reflected by the indistinctiveness of the OS/RPE (COST) line and the absence of foveal bulge and that abnormalities in the IS/OS junction may follow these changes in the more advanced stages. So et al [133] also reported loss of the OS/RPE (COST) line in acute phase AZOOR. In the acute phase, selective loss of the IS/OS and the OS/RPE (COST) lines corresponded with reduced visual acuity and mfERG potentials in areas of visual field defects.…”
Section: Acute Phasementioning
confidence: 93%
“…Loss of photoreceptor bodies (ONL) and outer segments with corresponding visual field defects as well as reduced visual acuity and mfERG potentials [127][128][129][130][131] Peripapillary IS/OS junction line defects in eyes with blind spot enlargement [130] Loss of the IS/OS junction line at the junctional areas between preserved and severely damaged retina [130] Thinning of inner nuclear layers [130] Indistinctiveness of OS/RPE (COST) line and absence of foveal bulge [132,133] Normal choroidal thickness [131] Recovery phase…”
Section: Acute Phasementioning
confidence: 99%
“…Some experts feel that AZOOR is a unique entity that may be more precisely defined by multimodal imaging: 1) autofluorescence, demonstrating characteristic zonal degeneration of the outer retina and RPE, typically beginning around the nerve and progressing to the periphery, and 2) high-definition spectral domain OCT, showing zonal or annular loss of the photoreceptor layer and IS/OS complex. 81,143,184,199,263,267 5.2.…”
Section: Acute Zonal Occult Outer Retinopathymentioning
confidence: 99%
“…Initially, minimal or no fundus changes occur, but enlarged blind spots, abnormalities on electroretinograms (ERGs) and permanent visual field loss often occur in this slowly progressing form of retinal pigment epithelium degeneration [1, 2]. Optical coherence tomography (OCT) images from eyes with AZOOR show a loss or irregularity of the photoreceptor inner segment/outer segment (IS/OS) line in areas corresponding to reduced multifocal ERG (mfERG) responses and visual field defects [3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. Recently, the cone outer segment tip (COST) line has been recognized as a thin, highly reflective line located between the IS/OS junction and the retinal pigment epithelium [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the cone outer segment tip (COST) line has been recognized as a thin, highly reflective line located between the IS/OS junction and the retinal pigment epithelium [16]. To our knowledge, there are few reports in the literature describing the abnormalities of the COST line in AZOOR [8]. However, there are several detailed reports about AZOOR patients who showed subjective and objective improvements in visual function [4, 8, 9, 10, 11, 12, 13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%